Genetic diversity among East African highland bananas for female fertility - Ssebuliba, R.N.; Rubaihayo, P.R.; Tenkouano, A.; Makumbi, Dan; Talengera, D.; Magambo, M. (2005)
There are 84 distinct cultivars of highland bananas (Musa spp.) in Uganda, grouped in five clone sets and it is not known which among these are female fertile. The objective of the study reported herein was to identify female fertile highland bananas that can be used in a cross breeding program and to determine the influence of pistil morphological traits on seed set. Seventy eight cultivars were screened for female fertility using pollen from ‘Calcutta 4\' and thirty-three cultivars representing the major variability of highland bananas were selected for studying pistil morphological traits to establish their relationship with seed yield. The clone sets and cultivars were highly significantly (P<0.0001) different in seed set rates but between-clone effects were higher than within-clone effects. Number of seeds was significantly negatively correlated with style length, ovary length and diameter of the style base. Path analysis indicated a high residual, suggesting that the traits analysed had little influence on female fertility. Nevertheless, style length was the most important trait in determining seed set because it had the strongest direct effect. Abnormalities in pistil morphological traits render cultivars female sterile.